Th17 and Regulatory T Cells in Mediating and Restraining Inflammation - Littman, Dan R.; Rudensky, Alexander Y. (Cell, 2010)
The vertebrate immune system is poised in a state of equilibrium that permits accurate and rapid protective responses against pathogens but curtails potential for causing harm to the host through targeting of “self” and provoking overexuberant inflammatory processes. In this Review we discuss this balance achieved in large part by interactions of different classes of T lymphocytes that have potent pro- or anti-inflammatory activity in the context of genetic and environmental factors, particularly the commensal microbiota.